2019
DOI: 10.1108/itp-04-2017-0133
|View full text |Cite
|
Sign up to set email alerts
|

Fostering work engagement in geographically-dispersed and asynchronous virtual teams

Abstract: Purpose The purpose of this paper is to explore the factors that enable work engagement to develop when asynchronous communication is used in virtual team (VT) projects. Design/methodology/approach Using a qualitative approach, a longitudinal study of an eight-month long VT project was carried out. Data collected included an extensive e-mail archive, project documentation, observation of team meetings and interviews with project members and leaders. Findings The findings show that VT leaders can actively p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 47 publications
1
51
0
1
Order By: Relevance
“…Differences concerning the self-image as a leader and the perceived responsibility also became apparent in Echterhoff’s study [ 72 ]. Higher requirements placed on leaders of virtual teams, amongst other things due to more intensive relationship design and maintenance, were also illustrated in further studies [ 17 , 18 , 33 ].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Differences concerning the self-image as a leader and the perceived responsibility also became apparent in Echterhoff’s study [ 72 ]. Higher requirements placed on leaders of virtual teams, amongst other things due to more intensive relationship design and maintenance, were also illustrated in further studies [ 17 , 18 , 33 ].…”
Section: Discussionmentioning
confidence: 71%
“…Nearly all leaders named communication on health-related topics as a central health-oriented leadership behavior. Previous studies had also emphasized the choice of a suitable communication medium in terms of richness for virtual communication [ 14 , 16 , 25 , 33 ]. In particular, the (re)design of tasks, emotional support, communication of expectations and offers of help were named as effective ways of dealing with exhausted employees [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reach that, e-leaders have to develop trust in their relationships, allowing greater exchange of ideas; they encourage information flow, and generate creative solutions (Avolio et al, 2014). Likewise, findings of Panteli et al (2019) showed that e-leaders boost employees' work engagement through effective use of resources and their attitude of development, support, and nourishment. These properties are helpful in contexts characterized by greater geographic distance, diversity, some ambiguity, and unfamiliarity with remote working.…”
Section: E-leadership Teleworking and Virtual Teamsmentioning
confidence: 99%
“…Hierzu zählen Beschleunigung, Komplexität, fehlende Benutzerfreundlichkeit, Unterbrechungen, eine Omni-und Dauerpräsenz, ein Kommunikationsrauschen durch IKT sowie eine Unzuverlässigkeit durch technische Probleme [29]. Die Veränderungen der flexibilisierten Arbeitswelt beeinflussen auch die Einflussmöglichkeiten von Führung [40] und stellen erhöhte Anforderungen an virtuelle Führungskräfte [1,5,16,34,42].…”
Section: Gesundheitsförderung In Virtueller Teamarbeit Durch Gesundheunclassified